2008
DOI: 10.1007/s11104-008-9763-5
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary diagnosis and recommendation integrated system (DRIS) model for diagnosing the nutrient status of sweet potato (Ipomoea batatas)

Abstract: Critical leaf nutrient concentrations have often been used to diagnose the nutritional causes of crop underperformance. Unfortunately, these diagnostic criteria are not available for mature, tuber-bearing sweet potato plants (the word 'tuber' being used to describe a swollen root rather than a swollen stem).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 18 publications
0
21
0
2
Order By: Relevance
“…It is feasible to find on literature some crops on which DRIS had already been used to assess the nutritional status of plants, such as; pineapple (Sema et al, 2010), cotton (Silva et al, 2009;Serra et al, 2010a,b;Serra et al, 2012), rice (Guindani et al, 2009), potato (Bailey et al, 2009Ramakrishna et al, 2009), coffee (Nick, 1998), sugarcane (Elwali & Gascho, 1984;Reis Jr & Monnerat, 2002;Maccray et al, 2010), orange (Mourão Filho et al, 2004), apple (Natchigall et al, 2007a,b), mango (Hundal et al, 2005), corn (Reis Jr, 2002;Urricariet et al, 2004), soybean (Urano et al, 2006(Urano et al, , 2007, Eucalyptus (Wadt et al, 1998), among other crops.…”
Section: Diagnosis and Recommendation Integrated System (Dris)mentioning
confidence: 99%
“…It is feasible to find on literature some crops on which DRIS had already been used to assess the nutritional status of plants, such as; pineapple (Sema et al, 2010), cotton (Silva et al, 2009;Serra et al, 2010a,b;Serra et al, 2012), rice (Guindani et al, 2009), potato (Bailey et al, 2009Ramakrishna et al, 2009), coffee (Nick, 1998), sugarcane (Elwali & Gascho, 1984;Reis Jr & Monnerat, 2002;Maccray et al, 2010), orange (Mourão Filho et al, 2004), apple (Natchigall et al, 2007a,b), mango (Hundal et al, 2005), corn (Reis Jr, 2002;Urricariet et al, 2004), soybean (Urano et al, 2006(Urano et al, , 2007, Eucalyptus (Wadt et al, 1998), among other crops.…”
Section: Diagnosis and Recommendation Integrated System (Dris)mentioning
confidence: 99%
“…1). Details about the landscape, vegetation, climate and sweet potato cultivation in the region are given in the previous paper by Ramakrishna et al (2008).…”
Section: Survey Location and Characteristicsmentioning
confidence: 99%
“…In a previous study, Ramakrishna et al (2008) used data from a limited number (56) of 'highyielding' planting stations in the 2005 survey to develop a diagnosis and recommendation integrated system (DRIS) model capable of evaluating the N, P, K and S statuses of sweet potato crops. In the present study, this model will be used to calculate DRIS N, P, K and S indices for all 203 planting stations.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure on land resources has increased dramatically because of the population growth; fallow periods between cropping cycles have been shortened from several decades to less than 1 year in the recent past. Such decline in soil fertility and productivity induced by land use change has been reported in Africa, Mediterranean regions and Asia (Biro et al, 2013;Abu Hammad and Tumeizi, 2012;Liu et al, 2014) Previous work conducted across four of the highland provinces (Southern Highlands, Eastern Highlands, Simbu and Enga) established potassium (K) deficiency as the major nutrient-related cause for the poor sweet potato productivity in almost a third of sweet potato farms Ramakrishna et al, 2009;Walter et al, 2011). These studies also reported that K deficiency was more of a problem in old farms (which have been cropped for several crop cycles) than in new farms (which are ready for cropping after fallow periods).…”
Section: Introductionmentioning
confidence: 96%